Interaction of nanoplastics with metronidazole and ciprofloxacin: The Trojan Horse effect. - Emiliano Perez-Sanchez; Ana Martínez (PLoS ONE)
Microplastics and nanoplastics are everywhere, but little is known about their chemical reactivity. In this study we performed a Density Functional Theory study of polystyrene (PS, a common non-biodegradable thermoplastic polymer) and polylactic acid (PLA, a biodegradable polymer) to understand the capacity to react of these two nanoplastics. The chemical reactivity of these oligomers is investigated through their capacity to either donate or accept electrons and, therefore, their capacity to oxidize other molecules. To model nanoplastics, we used oligomers formed with different numbers of carbon atoms. PLA is a better electron acceptor than PS, which could be related to oxidation reactions. It has also been reported that the presence of micro- and nanoplastics in the environment increases the bioaccumulation of pharmaceuticals such as antibiotics. To investigate this idea, we calculated the interaction energies of PLA and PS oligomers with two antibiotics: ciprofloxacin and metronidazole. The results indicate that both can form stable compounds with these two antibiotics. This might be related to the Trojan horse effect, which refers to the idea that the presence of nanoplastics increases the bioaccumulation of drugs. These results contribute to understand the reactivity of these nanoplastics.